2020
DOI: 10.1080/15428052.2020.1732253
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Attitudes and Reactions to Unfamiliar Food Pairings: An Examination of the Underlying Motivations and the Impact of Culinary Education

Abstract: A mixed �-methodology study was conducted to better understand consumer attitudes and behaviors toward novel food pairings and the impact of culinary education. Focus groups were conducted to investigate the underlying motivational factors to the reactions and behaviors toward unfamiliar foods. The second phase of the study consisted of sensory evaluation by two separate cohorts, panelists with and without culinary education, of food products created through the novel pairings of foods. Panelists with culinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The animal origin of food items has been found to affect perceived disgustingness by Traynor, Moreo, Cain, Burke, and Barry-Ryan [ 52 ]. They found that odor evaluation differed depending on the knowledge of the origin of the food item (animal origin was deemed to be more disgusting when knowledge of the origin was presented).…”
Section: Discussionmentioning
confidence: 99%
“…The animal origin of food items has been found to affect perceived disgustingness by Traynor, Moreo, Cain, Burke, and Barry-Ryan [ 52 ]. They found that odor evaluation differed depending on the knowledge of the origin of the food item (animal origin was deemed to be more disgusting when knowledge of the origin was presented).…”
Section: Discussionmentioning
confidence: 99%
“…The topics of consumer propensity and behavior toward the consumption of novel foods intersected. In this regard, it emerged that there were several studies on the factors that may influence the perception and behavior of the consumer (Dragone and Ziebarth, 2017;Specht et al, 2019;Coderoni and Perito, 2021;Traynor et al, 2021) and how consumers react to novel ingredients.…”
Section: Vosviewer Discussionmentioning
confidence: 99%
“…Consumers are sensitive to the modification of the expected texture. Traynor et al [ 48 ] emphasize that besides intrinsic sensory properties, extrinsic motivation like emotional reactions have a significant effect on the acceptance of novel foods.…”
Section: Discussionmentioning
confidence: 99%
“…There is no comprehensive sensory and consumer research in the literature [ 2 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] on the molecular and Note by Note meals in both cognitive impression and hedonic terms, which requires a special methodological approach.…”
Section: Introductionmentioning
confidence: 99%